1996
DOI: 10.1007/bf02253579
|View full text |Cite
|
Sign up to set email alerts
|

Territrems: Naturally occurring specific irreversible inhibitors of acetylcholinesterase

Abstract: Between 1983 and 1994, we studied renal function and neonatal conditions for eight pregnancies and births to six women who had received renal transplants in order to assess the effect of an allograft on pregnancy and its outcome. The gestation period was 34 to 39 weeks (mean 36 weeks and 4 days), and four pregnancies ended before term. All eight babies were delivered by cesarean section. Intrauterine growth retardation (IUGR) was found in both babies of one woman who had been treated with conventional (without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…DISCUSSION In our previous study of TRB inhibition on AChE extracted from the head of Helicoverpa zea, we observed an irreversiblelike inhibition (13). We also reported that although dialysis or dilution recovers the activity of BW284C51-inhibited eel AChE, the same treatment has no effect on TRB-inhibited eel AChE (14). In the present kinetic investigation, we reaffirmed these earlier observations of irreversible AChE inhibition by using very diluted TRB during the preincubation period (Fig.…”
Section: Fig 8 Dose-response Inhibition Of Ache and Bche By Trb Or supporting
confidence: 88%
See 4 more Smart Citations
“…DISCUSSION In our previous study of TRB inhibition on AChE extracted from the head of Helicoverpa zea, we observed an irreversiblelike inhibition (13). We also reported that although dialysis or dilution recovers the activity of BW284C51-inhibited eel AChE, the same treatment has no effect on TRB-inhibited eel AChE (14). In the present kinetic investigation, we reaffirmed these earlier observations of irreversible AChE inhibition by using very diluted TRB during the preincubation period (Fig.…”
Section: Fig 8 Dose-response Inhibition Of Ache and Bche By Trb Or supporting
confidence: 88%
“…In the experiment with NaCl or Triton X-100, the working enzyme solution contained 1 M NaCl or 1% Triton X-100. Enzyme activity was determined as described previously (14) and according to the colorimetric method of Ellman et al (25). The concentration of the catalytic subunit of AChE in the working enzyme solution was calculated using a molar catalytic efficiency of 6.0 ϫ 10 5 M acetylthiocholine hydrolyzed/ min at 25°C (26).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations